Student Learning Motivation in Biology Lessons at SMA Negeri 4 Pekanbaru - Putri, Sahira Askia; Putra, Riki Apriyandi; Firdaus LN, Firdaus LN (FKIP - Universitas Riau, 2024)
Learning motivation is the drive that a person has to be able to carry out learning activities so that it is an important thing that every student must have because it is the key to success in determining the level of student learning success. The phenomenon of low student learning motivation is certainly an obstacle in the learning process. Based on observations made through interviews with guidance and counseling teachers, distribution of pre-research questionnaires to students and findings from other researchers show that at SMA Negeri 4 Pekanbaru the phenomenon of low student learning motivation is still found. This research aims to obtain an overview of students' learning motivation profiles in biology lessons at SMA Negeri 4 Pekanbaru. This research uses a descriptive research design with a quantitative approach and survey method (online). The sample for this research was students from SMA Negeri 4 Pekanbaru class X, XI and class Data analysis through calculating the mean student learning motivation in biology lessons in terms of six learning motivation indicators. Based on the researchers' findings, it can be concluded that students' learning motivation in biology lessons at SMA Negeri 4 Pekanbaru is classified as medium.